The Effect of Toxic Leadership on Deviant Work Behavior: The Mediating Role of Employee Cynicism (Texas Journal of Multidisciplinary Studies, 2023)
This study explores the mediator role of The cynicism organizational (Cognitive Cynicism , Emotional Cynicism , Behavioral Cynicism)in relationship between the toxic leadership and the deviant work behavior(Property Deviance, Production Deviance). Furthermore, it is analyzed how cynicism organizational mediator role of The cynicism organizational in relationship between the toxic leadership and the deviant work behavior By using the original survey data from 716 employees in Marjan Hospital in Hilla. our results confirm that There is a positive significant effect of toxic leadership dimensions represented in each of (abusive supervision, narcissism, self-promotion, difficulty in predicting, authoritarianism) on organizational cynicism dimensions represented in each of (cognitive cynicism, emotional cynicism, behavioral cynicism).